A Study of Consumer Buying Behaviour of FMCG Products in Calicut City (With Special Reference of Tooth Paste) (International Journal of Scientific Research and Management (IJSRM), 2017)
Tooth paste are fast moving consumer goods that have seen a surge in their sales in the past few decades in India more and more people are opening up to the idea of experimenting and trying out newer Tooth paste. This study is attempt to cover the various factors that influence the buying decision of consumers who plan to purchase and or used Tooth paste. FMCG sector is the fourth largest sector in India touching everybody life’s in every day. The FMCG goods sector is vital contributor to India’s gross domestic products. The field of consumer behavior is the study of individual, group, organization and the process is used to select, secure, use and dispose of products and services that satisfies their needs. The Indian Tooth paste industry includes about 700 companies with combine annual revenue about 17 billion and also spread all the major metropolitan cites. India per capita consumption of Tooth paste is at 460 grm. Per annum. The Indian market capitalization of Tooth paste industries is 70% of India’s population resident in rural area and 50% Tooth pastes are sold in rural market. To attain this objective, a survey was developed and administered across various part of Calicut city.